A novel synthetic activator of Nurr1 induces dopaminergic gene expression and protects against 6-hydroxydopamine neurotoxicity in vitro. (21st October 2015) - Hammond, Sean L.; Safe, Stephen; Tjalkens, Ronald B.
Highlights: Loss of dopaminergic neurons in PD is associated with decreased expression of Nurr1. A synthetic Nurr1 activaor (C-DIM12) induces Nurr1 and DA gene expression in cell lines and primary neurons. C-DIM12 increases protein levels of exogenously expressed human Nurr1 in transfected neurons. Nurr1 RNAi prevents the inductive effects of C-DIM12 in neurons. C-DIM12 protects neurons from 6-hydroxydopamine toxicity. Abstract: Degeneration of dopaminergic neurons in Parkinson's disease (PD) is associated with decreased expression of the orphan nuclear receptor Nurr1 (NR4A2), which is critical for both homeostasis and development of dopamine (DA) neurons. The synthetic, phytochemical-based compound, 1, 1-bis (3′-indolyl)-1-( p -chlorophenyl) methane (C-DIM12) activates Nurr1 in cancer cells and prevents loss of dopaminergic neurons in the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) model of PD in mice. In the present study, we examined the capacity of C-DIM12 to induce expression of Nurr1-regulated genes in two dopaminergic neuronal cell lines (N2A, N27) and to protect against 6-hydroxydopamine (6-OHDA) neurotoxicity. C-DIM12 induced expression of Nurr1-regulated genes that was abolished by Nurr1 knockdown. C-DIM12 increased expression of transfected human Nurr1, induced Nurr1 protein expression in primary dopaminergic neurons and enhanced neuronal survival from exposure to 6-OHDA. These data indicate that C-DIM12 stimulates neuroprotective expression Nurr1-regulated genes in DA neurons.